Nutrient sensing in the nucleus of the solitary tract mediates non-aversive suppression of feeding via inhibition of AgRP neurons - Anthony H. Tsang; Danae Nuzzaci; Tamana Darwish; Havish Samudrala; Clémence Blouet (Elsevier, 2020)
The nucleus of the solitary tract (NTS) is emerging as a major site of action for the appetite-suppressive effects of leading pharmacotherapies currently investigated to treat obesity. However, our understanding of how NTS neurons regulate appetite remains incomplete. Objectives: In this study, we used NTS nutrient sensing as an entry point to characterize stimulus-defined neuronal ensembles engaged by the NTS to produce physiological satiety. Methods: We combined histological analysis, neuroanatomical assessment using inducible viral tracing tools, and functional tests to characterize hindbrain-forebrain circuits engaged by NTS leucine sensing to suppress hunger. Results: We found that NTS detection of leucine engages NTS prolactin-releasing peptide (PrRP) neurons to inhibit AgRP neurons via a population of leptin receptor-expressing neurons in the dorsomedial hypothalamus. This circuit is necessary for the anorectic response to NTS leucine, the appetite-suppressive effect of high-protein diets, and the long-term control of energy balance. Conclusions: These results extend the integrative capability of AgRP neurons to include brainstem nutrient sensing inputs.